AUTOMATION OF ACCOUNTING THE NUMERIC PARTS AND UNITS AT MANUFACTURING ENTERPRISES - E. S. Vasev; S. V. Kashin (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. The substantiation of the need and disclosure of the substantive and technological features of the design and  development of an information system for the registration of numeric parts and units at a manufacturing enterprise.Methods. Case-technology,object-oriented programming.Results. The development mechanism of an information system for registering numeric parts and units at a manufacturing enterprise is  described. The development process begins with an analysis of the  subject area, wherein the requirements for the information system  are defined. Two business processes related to the activity of the  production preparation engineer are identified and the entities and  types of these attributes are indicated. Using the case-tool  DBdesigner 4, a data scheme is constructed and code is generated for scripts used to create a database in the SQL language. The database is implemented on MySQL. The web-interface of the  information system is designed: website scheme, action sequence  diagram, website logical structure and layout. The resulting data  scheme is implemented within MySQL data base management  system (DBMS) and a web-based system interface developed using  object-oriented programming using Notepad ++ text editor. The  web-interface allows a multi-user working mode to be provided with the information system. The separation of basic and summary data among different tabs is performed in order to simplify the work of personnel and minimise the human factor associated with the processing of disparate data. The requirements to be met by the developed information system are defined.All software used in the development process is free.Conclusion. The selection of software tools for the development of a system for accounting of numeric parts and units at a manufacturing enterprise is implemented, allowing the conceptual, logical and physical design of a database – as well as its web  interface – to be developed. All stages for creating an information system were realised.